2011
DOI: 10.1016/j.jaut.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of autoimmune thyroiditis: The first decade

Abstract: Most of our current understanding of the genetic predisposition to autoimmune disease can be traced to experiments performed in the decade from 1971 to 1981. Chella David was a key contributor to this research. Many of these early steps came from studies of experimental autoimmune thyroiditis. This model has been especially valuable because essentially the same disease can occur spontaneously in selected strains of animals or can be induced by deliberate immunization. From a genetic point of view, the disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Indeed, one study among girls with TS (n = 84) showed that nearly 25% had clinical hypothyroidism and 40-50% had positive thyroid antibodies (antithyroperoxidase and antithyroglobulin antibodies) that are associated with Hashimoto's thyroiditis and Graves' disease [190]. The finding of increased rates of Hashimoto's thyroiditis in TS is not in line with the hypothesis that females with TS show more male-prevalent autoimmune diseases due to their X monosomy and with findings of increased production of antithyroid antibodies in females relative to males in animal models [191].…”
Section: Depression and Anxiety In Scasmentioning
confidence: 84%
“…Indeed, one study among girls with TS (n = 84) showed that nearly 25% had clinical hypothyroidism and 40-50% had positive thyroid antibodies (antithyroperoxidase and antithyroglobulin antibodies) that are associated with Hashimoto's thyroiditis and Graves' disease [190]. The finding of increased rates of Hashimoto's thyroiditis in TS is not in line with the hypothesis that females with TS show more male-prevalent autoimmune diseases due to their X monosomy and with findings of increased production of antithyroid antibodies in females relative to males in animal models [191].…”
Section: Depression and Anxiety In Scasmentioning
confidence: 84%
“…Expansion of TH1-polarized, autoreactive T-cells specific to thyroglobulin was found in E14 immunized ICA69 del/wt mice, suggesting that the progression of thyroid gland inflammation mediated by infiltrating ICA69-specific autoreactive T-cells can lead to the loss of immune tolerance against other thyroid autoantigens commonly associated with AITD. Hypothyroidism affects 5–10% of the general population with increased prevalence in older individuals and females [55,56]. The level of Ica1 mRNA transcripts in female B6 mice is twice as high as that of males, making the thyroid glands in females more sensitive to autoantigen ICA69 mediated autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Rose’s group were the first to show that susceptibility to the production of autoantibodies and thyroiditis are under independent genetic control, and that environmental factors could induce thyroid autoimmunity in genetically susceptible strains of animals [14,15]. Understanding how these genetic and environmental factors influence thyroid autoimmunity offers us the best opportunity to fully understand disease pathogenesis and, in turn, how this might be influenced for the benefit of patients.…”
Section: Hashimoto Legacymentioning
confidence: 99%
“…Observations in the early models of experimental autoimmune thyroiditis quickly demonstrated the importance of the major histocompatibility complex [MHC; in humans, this is the well-known human leukocyte antigen (HLA) system] in the predisposition of animals to this disorder, with the influence of additional non-MHC genes quickly becoming apparent [14]. At the same time, family studies in humans, such as those by my mentor Reg Hall and colleagues in Newcastle-upon-Tyne [19] confirmed that there was a genetic component to Hashimoto thyroiditis.…”
Section: Genetic Factorsmentioning
confidence: 99%